Spectral analysis of complete graph with infinite chains - Lebid, V.O. (Carpathian Mathematical Publications, 2014)
In the paper, the detailed spectral analysis of a complete graph with semibounded infinite chains is given. The spectrum of a self-adjoint operator which is generated by the adjacency matrix of the graph is defined, the spectral measure is constructed, eigenvectors and spectral expansion in eigenvectors are provided.